Neoadjuvanced chemotherapy for patients with advanced staged epithelial ovarian cancer - Hoang, Bao Nhan; Bach, Cam An; Le, Sy Phuong; Chau, Khac Tu; Tran, Thi Le Ha (Tạp chí Y học lâm sàng Bệnh viện Trung Ương Huế, 2016)
Objectives: To estimate the effects of neoadjuvant chemotherapy in patients with advanced stage ovarian cancer. Materials: 31 patients with stage III - IV ovarian cancer who were treated by neoadjuvant chemotherapy in department of Obstetrics and Gynecology of Hue Central Hospital, from January 2009 to December 2013. Method: A perspective study. Results: The median age was 53.8 ± 17.6. 87.1% of patients were staged III when first diagnosed. 19.4% of them responsed to the regimen and 83.9% reached optimal cytoreduction. Rate of recurrence is 25.8% and mean time intervals of recurrence is 8.6 ± 7.2 months. Conclusion: Neoadjuvant chemotherapy is one of the most effective treatments for patients with advanced stage ovarian cancer.